Current postgraduate education in neurosurgery in Argentina. Strategies for its improvement from a SWOT analysis.: https://doi.org/10.59156/revista.v37i01.497 - Mezzadri, Juan Jose; Campero, Alvaro; Tauro, Norma (Revista Argentina de Neurocirugía, 2023)
Summary: Postgraduate education in neurosurgery has been a constant concern since the beginning of the specialty. Currently active organizations in postgraduate education are the Asociación Argentina de Neurocirugía y el Colegio Argentino de Neurocirujanos. Both consider that medical residency is the most appropriate training system for a recently graduated doctor to become a specialist. To regulate and organize their pedagogical development, a reference framework was designed where the standards to be achieved were established, along with an accreditation program to achieve homogeneity of quality parameters, and fellowships were also created along with the regulations. for its accreditation, to complete the training in those aspects that were not sufficiently developed during the residency. Since professional certification is mandatory to practice, ad hoc courses were created that constitute the theoretical basis for both general neurosurgery and spinal surgery. Applicants must complete a series of requirements and go through different training instances that also include residence. To maintain the quality of medical care, a periodic revalidation or recertification program was created. The entire current situation was subjected to an analysis of its strengths, opportunities, weaknesses